2021
DOI: 10.1186/s12887-021-03022-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of diarrheal diseases among under five children in Jimma Geneti District, Oromia region, Ethiopia, 2020: a case-control study

Abstract: Background Globally, in 2017, there were nearly 1.7 billion cases of childhood diarrheal diseases, and it is the second most important cause of morbidity and mortality among under-five children in low-income countries, including Ethiopia. Sanitary conditions, poor housing, an unsanitary environment, insufficient safe water supply, cohabitation with domestic animals that may carry human pathogens, and a lack of food storage facilities, in combination with socioeconomic and behavioral factors, ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…Diarrhea is defined as the passage of three or more loose or watery stools within 24 hours, which might be manifested with the change in a person’s daily stool fluidity, frequency, or volume from what is considered normal. 1 , 2 Diarrhea is the leading cause of morbidity and mortality in children under the age of five worldwide, killing an estimated 533,768 children under the age of five in 2017. 3 , 4 According to the Ethiopian demographic and health survey report 2016, 13% of under-five children had diarrhea within two weeks preceding the survey, 5 and the third killer of under-five children in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhea is defined as the passage of three or more loose or watery stools within 24 hours, which might be manifested with the change in a person’s daily stool fluidity, frequency, or volume from what is considered normal. 1 , 2 Diarrhea is the leading cause of morbidity and mortality in children under the age of five worldwide, killing an estimated 533,768 children under the age of five in 2017. 3 , 4 According to the Ethiopian demographic and health survey report 2016, 13% of under-five children had diarrhea within two weeks preceding the survey, 5 and the third killer of under-five children in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Another study from Sidama region; southern Ethiopia reported the prevalence of diarrheal disease among under-five children ranged between 10.7 and 16.5% [ 9 ]. A study conducted in Jimma also reported sociodemographic, environmental, immunization status and behavioral factors are the main risk factors for diarrheal disease [ 10 ]. The same study also reported that children who were not vaccinated against rotavirus were about 2.5 times at risk of having diarrheal disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Jimma also reported sociodemographic, environmental, immunization status and behavioral factors are the main risk factors for diarrheal disease [ 10 ]. The same study also reported that children who were not vaccinated against rotavirus were about 2.5 times at risk of having diarrheal disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five moments are considered critical times to wash hands; after defecation, after handling child/adult feces or cleaning child's bottom, after cleaning the environment, before preparing food, and before eating food. 10 , 12 – 14…”
Section: Introductionmentioning
confidence: 99%
“…10 Five moments are considered critical times to wash hands; after defecation, after handling child/adult feces or cleaning child's bottom, after cleaning the environment, before preparing food, and before eating food. 10,[12][13][14] Evidence also shows that hand washing at critical times reduces rates of diarrheal diseases like cholera and dysentery by 41%. 15 It also has a better reward; 3.35 dollar investment in hand washing gives a backward benefit of 11.0 dollar investment in latrine construction, 200 dollar investment in water supply, and millions of dollars investment in immunization.…”
Section: Introductionmentioning
confidence: 99%